Does public debt impact economic growth in Zambia? An Ardl-bounds testing approach - Talknice Saungweme; Nicholas M. Odhiambo (SPOUDAI - Journal of Economics and Business, 2019)
This study examines the dynamic impact of public debt on economic growth in Zambia from 1970 to 2017. The study also estimated the relative impact of domestic public debt and foreign public debt on economic growth in Zambia. Using the autoregressive distributed lag (ARDL) bounds testing methodology, the results show that public debt has a positive impact on economic growth in Zambia, both in the short run and in the long run. The empirical results further reveal that the relative impact of public debt on economic growth in Zambia is dependent on the type of debt under consideration and is also time-invariant. Domestic public debt was found to be negatively related to economic growth, while its foreign counterpart had a positive impact, both in the short run and in the long run. To ensure sustainable economic growth and sustainable public debt levels, the study recommends the country to, among other things: 1) match financial resources with the country's absorptive capacity; 2) continuously and effectively manage its debt composition and structure to reduce currency and maturity risks; and 3) to continue with the implementation of structural and financial reforms in order to promote the efficient utilisation of public finance.
Keywords: H62; H63; O47; 330; Public debt; domestic public debt; foreign public debt; economic growth; Zambia; ARDL